1998
DOI: 10.1093/ndt/13.7.1799
|View full text |Cite
|
Sign up to set email alerts
|

Pre-emptive kidney transplantation: the attractive alternative

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 0 publications
3
40
1
5
Order By: Relevance
“…Analyses of data collected by the Collaborative Transplant Study and by the Oxford Transplant Centre demonstrate that the salutary impact of PRT on allograft survival is not continentspecific (7,12). These and other observational studies in aggregate demonstrate that PRT is associated with significant allograft and patient survival benefit for adult recipients (13)(14)(15).…”
Section: Survival Advantages Of Preemptive Transplantationmentioning
confidence: 53%
“…Analyses of data collected by the Collaborative Transplant Study and by the Oxford Transplant Centre demonstrate that the salutary impact of PRT on allograft survival is not continentspecific (7,12). These and other observational studies in aggregate demonstrate that PRT is associated with significant allograft and patient survival benefit for adult recipients (13)(14)(15).…”
Section: Survival Advantages Of Preemptive Transplantationmentioning
confidence: 53%
“…Be to, IIT taikymas pagerina pacientų gyvenimo kokybę, palyginti su ilgalaike dialize, nepriverčia prisirišti prie hemodializės centro ir yra pigesnis bei labiau ekonomiškai atsiperkantis gydymo būdas nei ilgalaikė pakeičiamoji inkstų terapija dializėmis. Ir vis dėlto nemažai privalumų turintis metodas nėra itin plačiai taikomas dėl iškylančių kliūčių, tokių kaip recipientų sąrašo sudarymo tvarka, donorų trūkumas, neaiškus tinkamiausias taikymo laikas [3][4][5][6][7][8][9][10][11][12]. 1980 metais išankstinė inkstų transplantacija JAV buvo atlikta 395 pacientams (2,2 proc.…”
Section: įVadasunclassified
“…Geriausia gydymo priemone pacientams, sergantiems lėtinės inkstų ligos galutine stadija, jau seniai pripažįstama inkstų transplantacija. Pastaraisiais dešimtmečiais atliekami tyrimai rodo, kad išankstinė inkstų transplantacija naudingumu lenkia visus kitus pakeičiamosios inkstų terapijos būdus, įskaitant ir transplantaciją po ilgalaikės dializės, ir turėtų būti laikoma geriausia gydymo priemone esant lėtinės inkstų ligos galutinei stadijai bei kuo plačiau taikoma [3][4][5][6][7][8][9][10][11][12]. IIT -mąstymo apie lėtinę inkstų ligą ir jos gydymą evoliucijos rezultatas.…”
Section: Kodėl Reikėtų Taikyti Išankstinę Inkstų Transplantaciją?unclassified
See 1 more Smart Citation
“…Early studies reported comparable graft and patient survival for preemptive transplant patients and patients transplanted after dialysis (3,4). More recent studies show that preemptive transplantation is associated with better patient and graft survival (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Additional advantages have been documented, such as avoidance of complications with dialysis access infections, reduced severity of sequelae of chronic kidney disease, increased ability to maintain employment, and decreased overall costs (16 -18).…”
mentioning
confidence: 99%